Tobacco Farming Using Organic and Inorganic Fertilizers Effect on Soil Quality in Migori County - Nyantika, M. M.; Sudoi, V.; Okeyo-Owuor, J. B.; Kisinyo, P. (Africa Environmental Review Journal, 2022)
In Kenya, tobacco is grown in several counties like Migori, Bungoma and Meru counties, the largest producer being China, followed by the USA and India. Whereas tobacco industry argues that tobacco cultivation is a lucrative economic venture for smallholder farmers, studies show the risks associated with tobacco growing outweigh its benefits. These includes the destruction of groundwater resource, river sedimentation systems, soil infertility among others. This study aims to assess effect of soil amendments – organic and inorganic fertilizers- on soil quality. The study was carried out in four sites in Migori County - Mabera, Bondo, Kakrao and Masaba. Tobacco was grown using inorganic fertilizer (DAP and CAN) (TF) at a recommended rate of 60 kg P/ha and 30 kg N/ha; organic fertilizer (manure) (TOM) was applied at recommended rate of 4 t/ha; and Control (TO). Tobacco was planted in a 10 m2 plots, laid in RCBD, with three replicates. Land preparation was done by hand digging using a hoe. Variety 583V was used in the four sites - Bondo, Kakrao, Mabera and Masaba. Normal agronomic practices were carried out throughout the experiment period. Data was collected management on tobacco yield. Soils data was also collected on soil pH, P, SOC and total N. Data was analyzed using GLM and subjected to ANOVA using GENSTAT 12. Means were separated using Tukeys at 5%. On average, soil pH at planting in season one was between 4.72 and 5.51. At harvest, soil pH measured between 4.57 to 5.41. In season two, there was no significant difference (p≤0.05) in the measured soil pH at planting. In season three, mean soil pH at planting stood at 4.89a under T. Masaba soils recorded the lowest soil pH mean under TF (4.72), followed by Kakrao (4.82). Generally, soil pH increased significantly (p≤0.05) TF and TOM when compared to the control, where pH levels decreased marginally. This indicates that high manure in the soil has the ability to absorb or bind hydrogen ions in its humic forms, whereas N fertilizers (DAP) add hydrogen ions to the soil, resulting in high acidity. Slight increase in pH in the control in season three may be due to H+ ions absorbed from the soil solution by humic substances. Highest mean tobacco yield in season two was recorded under TF. This was in Bondo in season two with a mean of 2.740 t/ha. Most high tobacco yields come from TF treatments which are in the forms of diammonium phosphate or DAP. The rapid growth of tobacco is due to phosphorus and nitrogen uptake. Excessive amounts H+ ions in reduced soil pH results to fixation and limitation of phosphorus uptake, and this has general adverse effects on tobacco yield. In conclusion, increasing the soil pH inhibited the growth of tobacco plants. Lower soil pH decreased the leaf weight by 0.3%-21.29%. Soil pH is an important factor that affects the growth of tobacco plants as well as the quality and yield of tobacco leaves, and this differs under different soils and climatic conditions.